Mexico: some aspects of popular preventive therapies - Miranda Videgaray, Carlos (1998)
The article presented here is the result of an anthropological approach to urban populations belonging to the middle and marginalized sectors in eight Mexican states, which we carried out for the Secretary of Health in 1994. This research was carried out in parallel to the second National Survey of Health (ENSA-11), seeking to delve into the meanings that mediate the processes of use of the different health services to which these social sectors have access.